Panchsheel and the Future: Perspectives on India-China Relations - C V Ranganathan Ed; RANGANATHAN (C V) Ed. (New Delhi Samskriti, 2005)
Celebrating the Golden Jubilee of the historicPanchsheel Agreement between India and China, this volume seeks to reviewaspects of the historical and cultural relations between India and China, and tobuild on the legacy of Panchsheel to chart areas of future Sino-Indiancooperation in economic relations, environmental management, and other areas ofmutual concern.
Keywords: International Relation; International Security; Economic Development